Non-bullous impetigo followed by erythema multiforme. - Caniato Serdeira, A.F. (European Journal of Pediatric Dermatology, 2020)
Erythema multiforme is a reaction pattern to numerous etiological factors; the history and some histological aspects suggest that it is a delayed-type hypersensitivity reaction. The triggering factors are numerous, especially viruses, and recently SARS-CoV2 (5) has been added to these. However, erythema multiforme can also be caused by bacteria such as Mycoplasma pneumoniae, Yersinia, Francisella tularensis, Legionella and Staphylococcus aureus (2, 4). Although some of these triggers, such as Herpes simplex virus, Staphylococcus aureus and Mycoplasma pneumoniae are very common in children, erythema multiforme is still a rare event in pediatric age. It is possible that only predisposed children have this pattern of reaction, as shown by some studies that associated Herpes simplex virus induced erythema multiforme with the human leukocyte antigen DQw3 (3). […]